Counseling on The Importance of Maintaining Women's Reproductive Health In Arjasa Village, Arjasa Sub-District, Jember District - Fajariyah, Susantin; Utami, Eva Tyas; Nihayah, Husnatun (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2025)
Women's reproductive health is an important aspect in maintaining community welfare, especially in preventing various diseases related to the reproductive organs. This counseling aims to increase the understanding and awareness of the community, especially mothers in Arjasa Village, about the importance of maintaining reproductive health. The method used in this activity is in the form of interactive counseling and discussion. The stages of service activities carried out: situation analysis, coordination with the village government, and implementation of activities. This activity involved 35 female participants aged 18-35 years, the majority of whom were housewives. The counseling material includes the definition of reproductive health, factors that affect it, common diseases, as well as prevention and early detection measures. The results of the activity showed that the participants had high enthusiasm in participating in the counseling, which could be seen from the active interaction during the question and answer session. The results of the activity showed a fairly good understanding of the counseling participants as seen from the enthusiasm of the participants in participating in the counseling and discussion sessions. The main obstacle in this activity was the limited time which caused some materials to be delivered briefly. Overall, this counseling has a positive impact in increasing awareness of women's reproductive health. It is expected that follow-up in the form of collaboration with village health cadres can continue to be carried out to maintain the reproductive health of the local community.